2001
DOI: 10.1054/bjoc.2001.1847
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TcR/CD3-zeta chain expression by a circulating factor derived from ovarian cancer patients

Abstract: SummaryIn women with ovarian cancer, suppression of components of the immune system may promote tumour development. Previous studies in ovarian cancer have demonstrated that decreased expression and function of the T-cell receptor (TcR)-associated signal transducing zeta-chain correlates with deficient immune responsiveness of T cells. In this study, sera and ascitic fluids obtained from woman with advanced ovarian cancer were found to suppress the expression of TcR-associated zeta chain. This suppression of z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…26,29,30 The present study reported how extrinsic soluble mediator OAS2 secreted by oral tumour cells modulate CD3-f chain expression in T cells. 38 The 2 0 5 0 -OAS, apart from its antiviral action is involved in other cellular processes such as cell growth and differentiation, gene regulation and apoptosis.…”
Section: Discussionmentioning
confidence: 58%
“…26,29,30 The present study reported how extrinsic soluble mediator OAS2 secreted by oral tumour cells modulate CD3-f chain expression in T cells. 38 The 2 0 5 0 -OAS, apart from its antiviral action is involved in other cellular processes such as cell growth and differentiation, gene regulation and apoptosis.…”
Section: Discussionmentioning
confidence: 58%
“…However, in patients with cancer or chronic infections such as leprosy or HIV, z expression may never recover to equal that in normal T cells (Stefanova et al, 1996;Zea et al, 1998), and its absence or partial loss in cancer patients appears to be substantially more common in tumour-infiltrating than in circulating T lymphocytes (Otsuji et al, 1996). Several different mechanisms have been proposed to explain the loss of z expression, including production of reactive oxygen metabolites (ROM) by tumour or tumour-associated monocytes (Kono et al, 1996;Otsuji et al, 1996), or by circulating activated granulocytes (Schmielau and Finn, 2001); apoptosis in the tumour microenvironment (Gastman et al, 1999;Hoffmann et al, 2002;; production and release by the tumour of z inhibitory proteins (Taylor et al, 2001); the availability of L-arginine in the microenvironment (Taheri et al, 2001) or increased degradation of z in chronically activated T cells (Penna et al, 1999). It is interesting to note that the loss of z was observed not only in the CD8 + CD45RA + CD27 À subset of effector cells, but also in other CD8 + T-cell subsets of patients with SCC of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…While the Fas/FasL pathway appears to participate in inducing apoptosis of CD4+ T cells in HIV (Badley et al, 1998) and of CD8+ T cells in cancer (Saito et al, 2000;Dworacki et al, 2001;Hoffmann et al, 2002), it is clearly not the only mechanism responsible for elimination of activated T cells. Among other factors that have been suggested are TNF/TNF-R, TRAIL/TRAIL-R (Srivastava, 2001), tumour-derived soluble factors (Taylor et al, 2001), and reactive oxygen metabolites (Hansson et al, 1999;Schmielau and Finn, 2001). In the case of patients with breast cancer we evaluated, utilisation of sFasL present in the plasma suggests its engagement in Fasmediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%